Customary Institutions in the Kei Indigenous Community Against Criminal Case Resolution - Rudini Hasyim Rado (Faculty of Law, Musamus University, 2020)
This research is focused on exploring the values of Kei customary law on the settlement of criminal cases that are resolved through customary institutions, by proposing 2 (two) problems, First, how is the existence of the law customary criminal Kei? Second, what is the role of customary institutions in the settlement of criminal cases? This research uses non-doctrinal legal research methods with interviews and observations as primary data. Meanwhile, data analysis is inductive and qualitative. It can be concluded that (1) the formal customary law of Kei is the values that live in the community that are agreed upon and are binding on the community, where the settlement of customary Kei crimes is taken in stages starting from the family level, customary institutions (Soa, Orang Kai and the last tier of Rat). (2) the role of traditional institutions in the settlement of criminal cases is starting to strengthen in society, this is indicated by the level of compliance with decisions and sanctions that are stipulated. People believe that customary cases are resolved by “insiders” (customary institutions) through deliberation (dok Tasdov) with a local wisdom approach to create social justice.